Treatment optimization for recurrent hepatocellular carcinoma: Repeat hepatic resection versus radiofrequency ablation - Liang‐He Lu; Jie Mei; Anna Kan; Yi‐Hong Ling; Shao‐Hua Li; Wei Wei; Min‐Shan Chen; Yong‐Fa Zhang; Rong‐Ping Guo (Cancer Medicine, 2020)
Abstract Background and aims The optimal treatment strategy for recurrent hepatocellular carcinoma (HCC) remains unclear. Therefore, we aimed to compare the outcomes of repeat hepatic resection (RHR) and radiofrequency ablation (RFA) for recurrent HCC. Method From December 2004 to December 2015, 138 patients who underwent RHR and 194 patients who underwent RFA were enrolled. Propensity score matching (PSM) was performed to establish 1:1 RHR‐RFA group matching. Clinical outcomes were compared before and after matching. Results Before matching, the 1‐, 3‐, and 5‐year postrecurrence survival (PRS) rates were 91.8%, 82.0%, and 72.9% for the RHR group (n = 138) and 94.4%, 75.4%, and 61.7% for the RFA group (n = 194), respectively (P = .380). After matching, the PRS rates at 1, 3, and 5 years were 90.5%, 81.5%, and 71.8% for the RHR group (n = 120) and 91.0%, 61.0%, and 41.7% for the RFA group (n = 120), respectively (P = .002). In the subgroup analysis, the PRS rates for the RHR group were better than those for the RFA group for patients who relapsed within 2 years (P = .004) or patients with primary tumor burden beyond the Milan criteria (P = .004). Multivariate analysis showed that treatment allocation was identified as an independent prognostic factor for PRS. Conclusion Compared with RFA, RHR provided a survival advantage for recurrent HCC, especially for patients who relapsed within 2 years and those with primary tumor burden beyond the Milan criteria.